In situ proteolysis of the Vibrio cholerae matrix protein RbmA promotes biofilm recruitment - Smith, Daniel R. (Proc Natl Acad Sci U S A, 2015)
The estuarine gram-negative rod and human diarrheal pathogen Vibrio cholerae synthesizes a VPS exopolysaccharide-dependent biofilm matrix that allows it to form a 3D structure on surfaces. Proteins associated with the matrix include, RbmA, RbmC, and Bap1. RbmA, a protein whose crystallographic structure suggests two binding surfaces, associates with cells by means of a VPS-dependent mechanism and promotes biofilm cohesiveness and recruitment of cells to the biofilm. Here, we show that RbmA undergoes limited proteolysis within the biofilm. This proteolysis, which is carried out by the hemagglutinin/protease and accessory proteases, yields the 22-kDa C-terminal polypeptide RbmA*. RbmA* remains biofilm-associated. Unlike full-length RbmA, the association of RbmA* with cells is no longer VPS-dependent, likely due to an electropositive surface revealed by proteolysis. We provide evidence that this proteolysis event plays a role in recruitment of VPS(−) cells to the biofilm surface. Based on our findings, we propose that association of RbmA with the matrix reinforces the biofilm structure and leads to limited proteolysis of RbmA to RbmA*. RbmA*, in turn, promotes recruitment of cells that have not yet initiated VPS synthesis to the biofilm surface. The assignment of two functions to RbmA, separated by a proteolytic event that depends on matrix association, dictates an iterative cycle in which reinforcement of recently added biofilm layers precedes the recruitment of new VPS(−) cells to the biofilm.